2021
DOI: 10.1186/s12889-021-10425-4
|View full text |Cite
|
Sign up to set email alerts
|

The injury mechanisms and injury pyramids among children and adolescents in Zhuhai City, China

Abstract: Background The unclear mechanisms and severity of injuries in the injury pyramids for Chinese children and adolescents prevent the prioritization of interventions. This study aimed to describe the injury mechanisms and injury pyramids in this population to provide a priority for injury prevention strategies. Methods Death, hospitalization, and outpatient/emergency department visit data from patients aged 0 ~ 17 years with injuries were obtained fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…However, the most common types of injuries in our region were falls, burns, road traffic injuries, poisoning, and foreign object injuries. These findings are not entirely consistent with that of domestic and foreign regions (12)(13)(14), which showed that burns and poisonings being less frequent. This variation may be due to our region have many mountainous areas, cold winters, and residents relying on burning charcoal for heat.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the most common types of injuries in our region were falls, burns, road traffic injuries, poisoning, and foreign object injuries. These findings are not entirely consistent with that of domestic and foreign regions (12)(13)(14), which showed that burns and poisonings being less frequent. This variation may be due to our region have many mountainous areas, cold winters, and residents relying on burning charcoal for heat.…”
Section: Discussioncontrasting
confidence: 75%
“…A cross-sectional survey from Egypt ( 25 ), a cohort study from Brazil ( 26 ) and a large-scale household survey involving more than one million people from Bangladesh ( 27 ) all indicated that falls were the predominant external cause of unintentional injury ( 13 ). Likewise, studies conducted in northwestern, southern, and Shanghai regions in China corroborated this finding ( 14 , 20 ). The possible reasons for this discrepancy are as follows: First, Central China, especially Henan Province, is a major agricultural province, producing a variety of nuts, which increases the risk of respiratory tract foreign bodies among children.…”
Section: Discussionmentioning
confidence: 52%
“…However, the occurrence and patterns of unintentional injuries vary significantly across regions and populations, depending on their geographic environment and economic status ( 10 12 ). Most of the reports on unintentional injuries in China have focused on the southwestern ( 13 ) and southern regions ( 14 ), while Central China, which had a large population (223 million) by the end of 2017, remains largely understudied. In this study, we conducted a multi-perspective analysis of hospitalized unintentional injury among children aged 0–18 years in Central China, to explore the temporal trends, and to recommend some preventive strategies and measures based on our findings.…”
Section: Introductionmentioning
confidence: 99%
“…This survey mainly referred to men, and elderly individuals in Jiangsu Province were more likely to be involved in RTIs (Ding et al, 2017 ). At the same time, RTIs and drowning were the two major causes of death among teenagers in China (Yin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%